Militær og mindfulness. Refleksioner over en uhellig alliance - Kotnis, Sita (Religionsvidenskabeligt Tidsskrift, 2015)
ENGLISH ABSTRACT: In recent years, mindfulness has become a major resource in the US military. This has provoked substantial criticism in American civil society, not least within contemplative environments. Considered as an expression of underlying Western ideas of contemplation and spirituality, this criticism may offer crucial insights into mindfulness as a modern, secular phenomenon. Based on long-term ethnographic fieldwork this article presents the empirical context of current military uses and adaptations of contemplative practises. The article also seeks to open the field for a closer investigation of the various configurations of ’ethics’ and ’meaning’ that underlie the criticism of the military appropriation. Finally, the article points out that the study of the possible dark sides of mindfulness, i.e. the potential to enhance injurious and harmful practices, is an under-researched as well as under-theorized field. DANSK RESUME: I det amerikanske militær er mindfulness i de senere år blevet en central ressource. Dette har affødt en del kritik i det amerikanske civilsamfund, ikke mindst i kontemplative miljøer – en kritik, der anskuet som udtryk for underliggende, vestlige forestillinger om kontemplation og spiritualitet, måske kan fortælle os noget centralt om mindfulness som moderne, sekulært fænomen. Med afsæt i et længerevarende etnografisk feltarbejde redegør denne artikel for den empiriske kontekst bag den samtidige militære anvendelse af kontemplative praksisser. Artiklen søger også at åbne op for en nærmere udforskning af de konfigurationer af ’etik’ og ’mening’, der ligger til grund for kritikken af den militære appropriering. Endelig påpeges det, at studiet af mindfulness’ mulige skyggesider, i form af potentialet til at optimere skadevoldende praksisser, er et både under-researchet og under-teoretiseret felt.